Served on a Silver Platter working Towards an Academic Research Data Concierge Service - Collura, Michael A.; Dressler, Virginia A; Hawkins, Michael; Kavulic, Michael (DESIDOC Journal of Library & Information Technology, 2019)
This article will discuss the development of a research concierge service aimed at supporting the unique data needs of researchers at each stage of the research lifecycle. Although based on work at one institution, a North American academic 4-year research university, the presented strategies are transferable to many different types of institutions. The concept behind this service emerged when staff members from the Office of Research, Information Technology, and University Libraries embarked on an endeavour, by way of a newly formed collaborative working group, to identify disparate research support services around campus. Steps will be suggested to assess and align existing support services as well as uncover gaps in service within an institution. A review of organisational models from other institutions with complementary services will also be included. The article will also examine the challenges faced by our institution in creating this collaborative group and the new service approach.